Effects of heavy-ion irradiation on the grain boundary chemistry of an oxide-dispersion strengthened Fe-12 wt.% Cr alloy - Marquis, E; Lozano-Perez, S; de Castro, V (2011)
Understanding the behaviour of oxide-dispersion strengthened (ODS) ferritic martensitic steels under irradiation is of prime importance in the design of future fusion reactors. Although changes in grain boundary chemistry during irradiation can significantly affect fracture strength, little is known on the behaviour of grain boundaries in ODS steels. Here, the effect of heavy-ion implantation at 500 °C on grain boundary chemistry in a model ODS Fe-12 wt.% Cr alloy was investigated using atom-probe tomography (APT) and analytical scanning-transmission electron microscopy ((S)TEM) techniques. While chromium and carbon segregation at grain boundaries is found in annealed alloys before irradiation, the three-dimensional APT reconstructions and TEM observations after irradiation reveal a complex distribution of Cr segregation and depletion at grain boundaries of varying character. © 2010 Elsevier B.V. All rights reserved.